La crise de Crimée (mars 2014) : comment en est-on arrivé là ? - Yann Richard (EchoGéo)
The Ukrainian crisis has various internal and external causes. And it is regrettable that this issue is addressed in the French press in very oriented way without really considering the Russian point of view, except to assert that president Putin boosted a new cold war and revives Russian imperialism. The annexation of the Crimea is undoubtedly a covert annexation. It is a coup as well as a clear rejection of the elementary requirements of international law. However, one must replace the crisis Crimean in its context to show that it did not come out of thin air. In this paper, we show that Russia, the United States and the European Union share some responsibility in this event. We also try to understand the ins and outs of the Russian position and why Vladimir Putin has taken this dangerous decision that isolates Russia and has negative effects on its economy.